2002
DOI: 10.1111/j.1349-7006.2002.tb01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Macrophage Migration Inhibitory Factor in Human Breast Cancer: Association with Nodal Spread

Abstract: Macrophage migration inhibitory factor (MIF) is known to exert pleiotropic functions including

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 39 publications
(46 reference statements)
9
73
0
Order By: Relevance
“…Similar to our findings in mouse melanoma cells, human melanoma cells were shown to overexpress MIF compared with normal melanocytes (7,8,17,18), and with a MIF antisense plasmid to inhibit MIF expression, tumor cell proliferation was suppressed in vitro (6). Recently, disruption of MIF signaling pathways has been shown to inhibit the growth and invasion of hormone-refractory prostate cancer cells (19).…”
Section: Discussionsupporting
confidence: 73%
“…Similar to our findings in mouse melanoma cells, human melanoma cells were shown to overexpress MIF compared with normal melanocytes (7,8,17,18), and with a MIF antisense plasmid to inhibit MIF expression, tumor cell proliferation was suppressed in vitro (6). Recently, disruption of MIF signaling pathways has been shown to inhibit the growth and invasion of hormone-refractory prostate cancer cells (19).…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, the PTEN-siRNA results in HeLa could indicate that, depending on other survival factors, MIF's prosurvival role may be most critical for a tumor cell, when the PI3K/Akt pathway is submaximally activated. Interestingly, it has been suggested that MIF may be particularly important in breast cancers with minimal nodal spread or with a node-negative phenotype and that MIF might play a role in tumor-stroma interactions of primary breast cancers (Bando et al, 2002). In support of such a notion, Hagemann et al (2005) have additionally implicated MIF in macrophageinduced invasiveness of epithelial breast cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, this system constituted a relevant cancer cell model, as MIF is strongly overexpressed in breast cancer and has been suggested to be associated with breast cancer development (Bando et al, 2002;Hagemann et al, 2005). Our results indicate that enhancement by MIF of Akt phosphorylation and survival is most marked in PTENand p53-negative breast cancer cells, whereas PTEN-and p53-positive breast cancer cells are unresponsive to exogenous MIF with respect to Akt activation and only seem to depend on MIF regarding their survival to a minor extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glioblastoma, neuroblastoma, colonic cancer and colorectal cancer have elevated levels of MIF (Shkolnik et al, 1987;Bacher et al, 2003;Ren et al, 2006;Lee et al, 2008). Through ELISA, it was found that the intratumoral level of MIF is indirectly proportional to the tumor involved loco-regional nodes (Bando et al, 2002). In bladder cancer, MIF expression stimulates the proliferation of urothelial tumor cells (Guo et al, 2011).…”
Section: Mif and Tumorsmentioning
confidence: 99%